(untitled) (Research, Society and Development, 2020)
After technological advances, data analysis for sports purposes has become of fundamental importance for tactical evolution and obtaining good results. In football, the use of these analyzes has been growing and bringing numerous benefits, both for the tactical development, as well as in the physical part of the athletes. In addition to tactical and technical collaboration for football, statistics are also widely used in predictions, ranging from a penalty kick to the final result of the game. The objective of this work is to find a model for predicting the results of soccer matches. Mandante (Mandante Team wins) Draw or Visitor (Visiting Team wins) using the Decision Tree method, where, after modeling the data and analyzing the accuracy of the model, which house would be more profitable was analyzed.